Human interface and the management of information : visual information and knowledge management thematic area, HIMI 2019, held as part of the 21st HCI International Conference, HCII 2019, Orlando, FL, USA, July 26–31, 2019, Proceedings,: visual information and knowledge management thematic area, HIMI 2019, held as part of the 21st HCI International Conference, HCII 2019, Orlando, FL, USA, July 26–31, 2019, Proceedings,. Part I / (2019) - Unknown
No abstract available